Optical Nanofabrication of Concave Microlens Arrays. Issue 5 (9th April 2019) - Liu, Xue‐Qing; Yu, Lei; Yang, Shuang‐Ning; Chen, Qi‐Dai; Wang, Lei; Juodkazis, Saulius; Sun, Hong‐Bo
Abstract: For the simple and versatile fabrication of nanosmooth finished microlens arrays on hard materials, an approach combining femtosecond laser modification with subsequent ion beam etching is demonstrated. This method is based on the dependence of the plasma etching rate on the laser fluence used to modify the surface. The fabricated microlenses exhibit a low surface roughness of approximately 2.5 nm, due to the high precision of the plasma etching and benefit from the smooth interface between the laser‐modified and pristine subsurface regions. Microlenses with focal lengths ranging from 60 to 100 µm are realized by controlling the laser fluence, exposure dose, and etching time. Uniform square and hexagonal microlens arrays are fabricated on both hard and ultrahard materials and glasses (fused silica, GaAs, SiC, diamond) by the same process and deliver high‐quality focusing and imaging. Abstract : Femtosecond laser modification followed by ion beam etching is proposed for simple and versatile fabrication of nanosmooth finished microlens arrays on hard materials. The fabricated microlenses exhibit a low surface roughness of approximately 2.5 nm. Uniform square and hexagonal microlens arrays are fabricated on fused silica, GaAs, SiC, and diamond by the same process and deliver high‐quality focusing and imaging.